Relationship between Illness Perception and Depressive Symptoms among Type 2 Diabetes Mellitus Patients in China: A Mediating Role of Coping Style - Jiarui Li; Xiaohui Qiu; Xiuxian Yang; Jiawei Zhou; Xiongzhao Zhu; Erying Zhao; Zhengxue Qiao; Yanjie Yang; Depin Cao (Journal of Diabetes Research)
Objective. The aims of the present study were to investigate the prevalence of depressive symptoms among type 2 diabetes mellitus (T2DM) patients in China and to explore how coping style influences the relationship between illness perception and depressive symptoms. Methods. Nine hundred and thirty-nine T2DM patients were recruited from a grade 3 Class A hospital in Harbin, China, and asked to complete a demographic questionnaire as well as the Self-rating Depression Scale (SDS), Brief Illness Perception Questionnaire-Revised (IPQ-R), and Medical Coping Modes Questionnaire (MCMQ). Hierarchical linear regression analysis and the bootstrap method were preformed to examine if coping style influenced the relationship between illness perception and depression. Results. The majority of patients (73.59%) exhibited depressive symptoms, including 37.27% with moderate and 6.71% with severe depressive symptoms. Depressive symptoms were more frequent in patients with complications (P<0.05). A resignation coping style partially mediated the influence of illness perception on depressive symptoms. Conclusions. Interventions to improve coping style may reduce the prevalence or severity of depressive symptoms among T2DM patients, potentially enhancing treatment adherence and clinical outcome.